In vitro and in silico Activity of Iridoids Against Leishmania amazonensis - Vendruscolo, Maria H.; das Neves, Gustavo Machado; Kagami, Luciano Porto; Rodrigues Junior, Luiz Carlos; Nunes Diehl, Maria Luísa; Gnoatto, Simone C. B.; de Loreto Bordignon, Sérgio Augusto; Romão, Pedro Roosevelt Torres; Eifler-Lima, Vera Lucia; von Poser, Gilsane Lino (Current Drug Discovery Technologies, 2019)
Background: Leishmaniasis reaches millions of people around the world. The control of the disease is difficult due to the restricted access to the diagnosis and medication, and low adherence to the treatment. Thus, more efficient drugs are needed and natural products are good alternatives. Iridoids, natural products with reported leishmanicidal activity, can be exploited for the development of anti- Leishmania drugs. The aim of this study was to isolate and to investigate the in vitro activity of iridoids against Leishmania amazonensis and to compare the activity in silico of these compounds with those reported as active against this parasite. Methods: Iridoids were isolated by chromatographic methods. The in vitro activity of asperuloside (1) and geniposide (2) from Escalonia bifida, galiridoside (3) from Angelonia integerrima and theveridoside (4) and ipolamiide (5) from Amphilophium crucigerum was investigated against promastigote forms of Leishmania amazonensis. Molecular modeling studies of 1-5 and iridoids cited as active against Leishmania spp. were performed. Results: Compounds 1-5 (5-100 μM) did not inhibit the parasite survival. Physicochemical parameters predicted for 1-5 did not show differences compared to those described in literature. The SAR and the pharmacophoric model confirmed the importance of maintaining the cyclopentane[C]pyran ring of the iridoid, of oxygen-linked substituents at the C1 and C6 positions and of bulky substituents attached to the iridoid ring to present leishmanicidal activity. Conclusion: The results obtained in this study indicate that iridoids are a promising group of secondary metabolites and should be further investigated in the search for new anti-Leishmania drugs.
Keywords: Iridoids